Tindakan Promotif Kesehatan Untuk Mengurangi Kasus Penyakit Degeneratif Dengan Pemanfaatan Buah-Buahan - Devi - Ratnasari; Ahsanal Kasasiah; Vesara Ardhe Gatera (Janaka, Jurnal Pengabdian Masyarakat, 2021)
The means to improve of public health can be carried out through promotive, preventive, curative and rehabilitative. Promotive are a series of efforts to provide learning experiences for individuals, families and communities to influence behavior, in order to maintain, and improve of health. Promotive activities can be carried out in the form of counseling to the community with the aim to increasing knowledge. This service aims to provide information to the public regarding the prevention of degenerative diseases by consuming fruits. The method used is in the form of lectures, questions and answers, and measuring the increase of public knowledge through questionnaires given before and after counseling. The target of this service is the residents and officials of Bengle Village, Karawang Regency. The result of this service activity is the increased of public knowledge about degenerative diseases.